Inherent toughness and fracture mechanisms of refractory transition-metal nitrides via density-functional molecular dynamics. (1st June 2018) - Sangiovanni, D.G.
Abstract: Hard refractory transition-metal nitrides possess unique combinations of outstanding mechanical and physical properties, but are typically brittle. Recent experimental results demonstrated that single-crystal NaCl-structure (B1) V0.5 Mo0.5 N pseudobinary solid solutions are both hard (∼20 GPa) and ductile; that is, they exhibit toughness, which is unusual for ceramics. However, key atomic-scale mechanisms underlying this inherent toughness are unknown. Here, I carry out density-functional ab initio molecular dynamics (AIMD) simulations at room temperature to identify atomistic processes and associated changes in the electronic structure which control strength, plasticity, and fracture in V0.5 Mo0.5 N, as well as reference B1 TiN, subject to <001> and <110> tensile deformation. AIMD simulations reveal that V0.5 Mo0.5 N is considerably tougher than TiN owing to its ability to ( i ) isotropically redistribute mechanical stresses within the elastic regime, ( ii ) dissipate the accumulated strain energy by activating local structural transformations beyond the yield point. In direct contrast, TiN breaks in brittle manner when applied stresses reach its tensile strength. Charge transfer maps show that the adaptive mechanical response of V0.5 Mo0.5 N originates from highly populated d - d metallic-states, which allow for counterbalancing the destabilization induced via tensile deformation by enabling formation of new chemical bonds. The high ionic character and electron-localization in TiN precludes the possibility of modifying bonding geometries to accommodate the accumulated stresses, thus suddenly causing material's fracture for relatively low strain values. Graphical abstract: Image 1